PCB Rogowski coil sensor by using saw blade pattern for arcing fault detection - Khalid, K.A.; Fahmi, M.I.; Nanyan, A.N.; Bohari, Zul Hasrizal (2023)
Rogowski is a special current transformer and has been categorised as a low-power stand-alone current sensor. This sensor is designed by using a Saw blade pattern with 50 turns and 100 turns. This number of turns will impact the increment of the sensitivity of the sensor. Rogowski coil is used for measuring the alternating current (AC) and high-speed current pulses. The PCB Rogowski Coil will detect the arcing fault that design with AutoCAD software after that import to CST software. An arc is created when the electrical current jumps the gap between two conductive materials. The most common causes of arcs include worn contacts in electrical equipment, damage to insulation, break in a cable and loose connections. In order to reduce the arc fault risk, the arc fault interrupter (AFI) technology and arc fault detectors (AFD) have been developed. However, these devices are most suitable for domestic application or low voltage (LV). This paper proposed a simulation using AutoCAD and CST software to design a Rogowski coil and the Rogowski Coil sensor will be tested by using CST software in terms of radiation pattern. The biggest radiation pattern in red colour is the saw blade pattern in 100 turns at 2 KHz frequency, the radiation pattern covering entire sensor area compared with other radiation patterns with other frequency. The main lobe magnitude for 2 KHz frequency is 46.8 dB, main lobe direction is 180 deg, angular width is 153.4 deg and the side lobe level is zero. This is the best number of turn and frequency compared to 50 turn saw blade sensor.